Pengetahuan dan Sikap Higiene dalam Konteks Pembuatan Jamu Tradisional: Studi Komparatif pada Peserta Pelatihan di Desa Kakor, Kecamatan Lembor Selatan - Dewi Sartika Umul; Andriano Calrinto Mami; Yulianus Janur (JURNAL AKADEMISI VOKASI, 2025)
This study aims to examine the effect of hygiene knowledge and hygiene attitudes on participants of a traditional herbal drink (Jamu Beras Kencur) training program in Kakor Village, Lembor Selatan District. The importance of hygiene practices in traditional food production, particularly in tourism-based community economies, served as the rationale for this research. The study used a quantitative explanatory approach with a saturated sampling technique, involving 30 participants comprising students and local residents. Data were collected through pre-test and post-test questionnaires and analysed using Partial Least Squares Structural Equation Modelling. The findings show a significant increase in participants’ hygiene knowledge and attitudes after the training. All measurement indicators met the standards for validity and reliability, and the analysis revealed a strong and statistically significant influence of hygiene knowledge on hygiene attitudes. The path coefficient was 0.984 with a coefficient of determination of 0.968. These results indicate that hygiene education through practical training effectively enhances both understanding and behavioural intention among participants. The findings highlight the crucial role of hygiene knowledge in shaping safe production behaviours, reinforcing the need for community-based interventions to support the development of quality local culinary products in tourism destinations